REGULATION OF TRANSACTIONS IN THE FIELD OF ELECTRONIC COMMERCE IN UZBEKISTAN - Abdurahmanov Abdumutal Abdujabborovich (Journals Park Publishing, 2023)
Currently, communication and the Internet are widely used throughout the world, which makes it possible to use the electronic circulation of many documents. The epidemiological situation that has developed in the world has significantly accelerated the process of electronic exchange of documents in all areas of government activity. We can say that the current epidemiological situation has prompted the business sector to actively respond to the changed situation and change the conditions and forms of relationships between business participants. The rapid development of e-commerce has led to an increase in the number of transactions both in international trade and in the domestic market. the development of e-commerce, the legal support of new trading channels for a number of segments of this institution, the features of the legal support of electronic payments, the creation of a legal regime for new e-commerce institutions, such as smart contracts, the issues of cryptocurrencies, NFTs, the participation of artificial intelligence in the economic activities.
Keywords: Electronic commerce, electronic transaction, electronic document, contracts, electronic data interchange, digital signature.